Selangor Mental Sihat (SEHAT) helpline: a digital mental health intervention for the advocacy and intervention of mental health - Rusli, Mohammad Farhan; Zainal Abidin, Muhammad 'Adil; Mohd Tohit, Nor Faiza; Abdul Khaiyom, Jamilah Hanum; Md Rosli, Ahmad Nabil; Ridzwan, Hijaz; Mohamad Fuad, Adha Radha Nasheha; Badrol Hisham, Afaf Qamelia; Zamzuri, Iman Aisha; Mahmud, Siti Mariah (Malaysian Public Health Physicians’ Association, UKM, 2023)
Introduction According to the World Health Organization (WHO), over 450 million people around the world are affected by mental disorders; with the estimation that one in four people experiences mental illness at some point in their lives.